Exploratory analysis on payment mechanisms to Community Mental Health Centers in Chile using mixed grounded theory - Toro-Devia, Olga; Alvarado, Rubén; Jeria, Mercedes; Razzouk, Denise; Salvador-Carulla, Luis (Medwave, 2024)
Introduction Research on psychiatric deinstitutionalization has neglected that reforms in this field are nested in a health system that has undergone financial reforms. This subordination could introduce incentives that are misaligned with new mental health policies. According to Chile’s National Mental Health Plan, this would be the case in the Community Mental Health Centers (CMHC). The goal is to understand how the CMHCpayment mechanism is a potential incentive for community mental health. Methods A mixed quantitative-qualitative convergent study using grounded theory. We collected administrative production data between 2010 and 2020. Following the payment mechanism theory, we interviewed 25 payers, providers, and user experts. We integrated the results through selective coding. This article presents the relevant results of mixed selective integration. Results Seven payment mechanisms implemented heterogeneously in the country’s CMHC are recognized. They respond to three schemes subject to rate limits and prospective public budget. They differ in the payment unit. They are associated with implementing the community mental health model negatively affecting users, the services provided, the human resources available, and the governance adopted. Governance, management, and payment unit conditions favoring the community mental health model are identified. Conclusions A disjointed set of heterogeneously implemented payment schemes negatively affects the community mental health model. Formulating an explicit financing policy for mental health that is complementary to existing policies is necessary and possible.